Governing Village Fund in Indonesia: Is It Eradicating Poverty? - Satria Aji Imawan; Erwan Agus Purwanto (Indonesian Association for Public Administration, 2020)
This study was conducted by its finding that there were inconsistencies and uncorrelated data from the government score-based report about Village Fund, and the public perception of the village fund. This research observes relevance of those numbers using the Impact Assessment concepts. This research can act as a useful insight for the governments, researchers and societies to evaluate the commitment of the government to build Indonesia from village. By using descriptive quantitative research method, this paper critically summarises the government report of the Village Fund by contrasted the priorities target of the fund. From the assessment, it was found that the development of the village facilities, infrastructure, and community empowerment program currently increased, but the village fund still has a problem with its equalisation and utilisation of the fund. In conclusion, the achievement numbers of the village fund do not have any correlation with the poverty reduction, because there are lack of equalisation and perception in some sectors. The perception index does not correlate with the satisfaction index in terms of infrastructure development, and the intervention of the village fund does not have a connection with the understanding of people on the use of the fund.